Marketing Technology (MarTech) for Customer Relationship Management: An Examination of the Theory - Practice Gap - Dilogini, S. (University of Kelaniya, 2025)
Customer Relationship Management (CRM) is most important area in the marketing. Now-a-days, Electronic Customer Relationship Management (e-CRM) is the outcome of changes in traditional marketing by integrating technologies of new electronic channels as called Marketing Technology through e-CRM practices. In the past decade, an increasing number of studies have investigated Internet Banking (IB) from the diffusion perspective, but there is a lack of research study on cumulative literature of innovation diffusion theory (IDT) which is related with existing e-CRM practices. This study tries to address and solve the issue that how far accessible theory which applies/puts in to real practices. It is an attempt to assess an application of IDT on existing MarTech practice on CRM in licensed commercial banks, Sri Lanka (SL). To achieve the objectives of the study primary data were collected through questionnaires from 400 Mobile Banking Application (MB app) customers in Sri Lanka. These respondents were selected using snowball sampling technique. The data were analyzed using descriptive statistical analysis, Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The results of the study indicated that, there are several applications of IDT theory on existing MarTech practices in CRM. Findings reveal that while IDT aligns with some CRM practices, limitations exist in areas like trialability, interpersonal communication, and customer persuasion. Recommendations are provided to bridge gaps between IDT and real-world e-CRM applications, aiding both academics and practitioners in enhancing MarTech effectiveness in banking.
Keywords: Electronic Customer Relationship Management (e-CRM); Innovation Diffusion Theory (IDT); Marketing Technology (MarTech); Mobile Banking Application (MB app); Theory - Practice Gap